A single-tier pension: What does it really mean? - Rowena Crawford; Soumaya Keynes; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2013)
A significant reform of the UK's state pension system is currently being enacted. From 2016-17, the basic state pension and state second pension will be replaced by a new single-tier pension for everyone below the state pension age (SPA). This will bring an end to earnings-related state pension accrual in the UK. This marks the latest step on a long, tortuous and rather circular journey - a journey that started in the early 1970s with a basic state pension worth about 145 a week (in current earnings terms) and that has finally ended up in much the same place. The major difference between the 1974 system and the proposed new system is that the new system will be essentially universal, with considerably more extensive crediting of unpaid activities than was available in 1974...
Keywords: 330